Horner syndrome in traumatic brachial plexus injury - Antonija Krstačić; Silva Butković Soldo; Ana Bulić; Goran Krstačić (Open Journal of Trauma - Peertechz Publications, 2020)
We report on a 29-year-old male patient, who presented at our clinic with mild left ptosis and miosis and with plegia of the left upper limb too. The patient also complained with severe crushing sensation and a constant burning over the left hand. He was injured in motorcycle collisions.